2019
DOI: 10.1002/advs.201970106
|View full text |Cite
|
Sign up to set email alerts
|

Nanotheranostics: Metal–Organic‐Framework‐Derived Carbon Nanostructures for Site‐Specific Dual‐Modality Photothermal/Photodynamic Thrombus Therapy (Adv. Sci. 17/2019)

Abstract: In article number 1901378 , Qi Yang, Huiyu Liu, and co‐workers develop a dual modality photothermal/photodynamic thrombolytic strategy via targeting nanoagents with GPIIb/IIIa receptors targeting agents, effectively breaking the fibrin skeleton and preventing high bleeding risk of systematic fibrinolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Our previous studies have shown that the generated ROS can disrupt phospholipids such as platelet factor 3. [ 28 ] Moreover, ROS could disrupt the fibrin skeleton, as assessed by fluorescein isothiocyanate (FITC)‐labeled fibrin clots assay. In Figure 4d, amount of collapsed skeleton and fragments were distinguished after incubating fibrin with nanoparticles and US irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that the generated ROS can disrupt phospholipids such as platelet factor 3. [ 28 ] Moreover, ROS could disrupt the fibrin skeleton, as assessed by fluorescein isothiocyanate (FITC)‐labeled fibrin clots assay. In Figure 4d, amount of collapsed skeleton and fragments were distinguished after incubating fibrin with nanoparticles and US irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…The artificial thrombus formed by fresh blood agglomeration with the help of calcium chloride and thrombin has been utilized for intuitive evaluation of thrombolysis ability in vitro. [ 25,45 ] Capillary thrombus and tail bleeding assay are also important in in vitro models for evaluating theranostic systems. [ 46 ] Thus, the active exploration of newly‐fashioned thrombus‐related disease murine models, such as mimetic thrombus detachment and migration, is another important avenue to push the clinical translation of fundamental research.…”
Section: Mouse Thrombosis and Thrombus‐related Disease Modelsmentioning
confidence: 99%
“…[ 13,16,114–117 ] Dual‐photothermal/photodynamic thrombolysis has also been reported using nanostructured porphyrin. [ 118 ]…”
Section: Stimuli‐mediated Thrombolysismentioning
confidence: 99%
“…One of the major criticisms of NIR‐induced photothermal thrombolysis is the risk of secondary embolism to small blood vessels by larger clot fragments. [ 118 ]…”
Section: Stimuli‐mediated Thrombolysismentioning
confidence: 99%
See 1 more Smart Citation